Analisis Beban Kerja Petugas Pada Unit Rekam Medis Di RSUD Pasar Rebo Jakarta Timur - Putra, Muhammad Dudayev Caesar; Andini, Hafida Sofa (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
Pasar Rebo Regional Hospital's medical records unit has not had a workload calculation for a long times, so it is very necessary to conduct a workload analysis calculation, to prevent excessive workload on medical records unit staff. The workload analysis calculation that was previously carried out also used WISN (Workload indicators of staffing need), which is no longer valid. This research is a descriptiv study using the ABK Kes method (Health Workload Analysis). The research was conducted in the medical records unit of Pasar Rebo Regional Hospital. The populations in this study was all medical record staff at Pasar Rebo Regional Hospital, totaling 46 people. The data in this study were analyz use the ABK Kes method to obtain the number of record staff needed at Pasar Rebo Regional Hospital. Based on the results of the calculations of staff needs using the ABK Kes method, the number of Human Resources needed for the medical records unit is 55 people. Thus, it can be conclude that the numbers of staff in the medical record unit at Pasar Rebo Regional Hospital does not match its needs, where Pasar Rebo Regional Hospital lacks 9 staff/officers in the medical records unit.